Interfacial stability control of MHD Bingham fluids in micro-porous MEMS structures via fractal analysis - El-Dib, Yusry O.; Mady, Amal A.; Alyousef, Haifa A. (Frontiers in Physics, 2025)
This study investigates Magnetohydrodynamics (MHD) interfacial stability in Bingham fluids moving in micro-porous MEMS structures with fractal space characteristics. The study uses nonlinear boundary conditions to study motion equations, resulting in a nonlinear partial differential equation for interface displacement with complex coefficients. The study also uses a modified Lindstedt-Poincaré transformation to express the elevation amplitude equation in fractal space, which is converted to a linear form using the harmonic equivalent linearization approach (HELA). The study presents diagrams to illustrate and interpret the resulting stability characteristics, providing valuable insights into interface stability under nonlinear and fractal effects. These results have direct application to fluid interface stability in microporous MEMS (microelectromechanical systems) devices, such as sensors, actuators, and microfluidic systems.